2022
DOI: 10.3390/ijms23147735
|View full text |Cite
|
Sign up to set email alerts
|

Limosilactobacillus reuteri Attenuates Atopic Dermatitis via Changes in Gut Bacteria and Indole Derivatives from Tryptophan Metabolism

Abstract: Gut bacteria are closely associated with the development of atopic dermatitis (AD) due to their immunoregulatory function. Indole derivatives, produced by gut bacteria metabolizing tryptophan, are ligands to activate the aryl hydrocarbon receptor (AHR), which plays a critical role in attenuating AD symptoms. Limosilactobacillus reuteri, a producer of indole derivatives, regulates mucosal immunity via activating the AHR signaling pathway. However, the effective substance and mechanism of L. reuteri in the ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…24 Furthermore, Fang et al's study demonstrates that treatment with L. reuteri DYNDL22M62 significantly induces the release of ILA, thereby further reducing the levels of Th2 cell cytokines and suppressing aberrant Th2-type immune responses in atopic dermatitis mice. 25 On the other hand, accumulating evidence supports the role of the indole derivatives in the maintenance of intestinal barrier integrity, which is primarily driven by AHR-mediated IL-22 generation and AHR-mediated intestinal stem cell differentiation. 7,[26][27][28] Furthermore, B. infantis-derived ILA can also inhibit the release of inflammatory cytokines in intestinal epithelial cells by activating the AHR and nuclear factor erythroid 2-related factor 2 (Nrf2) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, Fang et al's study demonstrates that treatment with L. reuteri DYNDL22M62 significantly induces the release of ILA, thereby further reducing the levels of Th2 cell cytokines and suppressing aberrant Th2-type immune responses in atopic dermatitis mice. 25 On the other hand, accumulating evidence supports the role of the indole derivatives in the maintenance of intestinal barrier integrity, which is primarily driven by AHR-mediated IL-22 generation and AHR-mediated intestinal stem cell differentiation. 7,[26][27][28] Furthermore, B. infantis-derived ILA can also inhibit the release of inflammatory cytokines in intestinal epithelial cells by activating the AHR and nuclear factor erythroid 2-related factor 2 (Nrf2) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Of the many indole derivatives currently under investigation [94][95][96][97], the work by Yu et al demonstrated the potential of indole-3-aldehyde treatments for lesional and nonlesional AD patients by attenuating skin inflammation and TSLP keratinocyte expression in an AD-like dermatitis murine model (MC903) [98]. More recently, Fang et al further emphasized the importance of microbially (Limosilactobacillus reuteri) produced indole derivatives (indole lactic acid and indole propionic acid) in attenuating AD by demonstrating its ability to suppress IgE, TSLP, IL-4 and 5 levels in mice [99]. Regarding the anti-inflammatory potential of hydrophilic bile acids (tauroursodeoxycholic acid (TUDCA)), reports have shown that they reduce the unfolded protein response (UPR) seen in keratinocytes [59,100], hypersensitivity in asthmatic patients, as well as reverse the amyloid beta-oxidation of mitochondrial membranes in Alzheimer's murine models [101,102].…”
Section: Restoration Of Microbial Homeostasismentioning
confidence: 99%
“…L. reuteri Fn041 regulated the intestinal flora and significantly inhibited AD symptoms by regulating the systemic ratio of Th1 and Th2 cytokines in mice ( Zhao et al., 2022 ). L. reuteri DYNDL22M62 attenuated AD symptoms by modulating gut bacteria in mice ( Fang et al., 2022 ). Mothers and their babies supplied with L. reuteri ATCC 55730 had a lower prevalence of IgE-associated eczema at 2 years of age ( Abrahamsson et al., 2007 ).…”
Section: Monostrain Lactobacillus In the Treatment...mentioning
confidence: 99%